Effect Of Vitamine AND Selenum On Immune Response Of CO - Baghdad Vaccine In Sheep. - A. M.H. AL-Judi; R. H. Hameed; A. D. Salman (The Iraqi Journal of Veterinary Medicine, 2004)
This study was done on 57 Awassi pregnant ewes, divided in to 5 groups, the 1st control group, the second group received